Register Variation in Word-formation Processes: The Development of -ity and -ness in Early Modern English - Rodríguez-Puente, Paula (International Journal of English Studies, 2020)
This paper traces the development of two roughly synonymous nominalizing suffixes during the Early Modern English period, the Romance -ity and the native -ness. The aim is to assess whether these suffixes were favored in particular registers or followed similar paths of development, and to ascertain whether the ongoing processes of standardization and vernacularization may have affected their diachronic evolution. To this purpose, the type frequencies and rates of aggregation of new types of the two suffixes were analyzed in seventeen different registers distributed along the formal-informal and the speech-written continua. Results indicate that -ness tends to lose ground in favor of -ity between the sixteenth and the eighteenth centuries, a change which seems to have begun in formal written registers and spread towards ‘oral’ ones, probably aided by a general trend in written registers for the adoption of a more learned and literate style during the eighteenth century.